VD_FINDINFO Jug / 2016 / 178 vom 31. März 2016 - VD Tribunal cantonal (2016)
CONTRAVENTION, CONTRAVENTION DE POLICE DE DROIT CANTONAL, JUGE UNIQUE, FRAIS DE LA PROCÉDURE | 106 CP, 398 al. 4 CPP (CH), 426 al. 1 CPP (CH)